Correlation between Pollutant Parameters Temperature, pH, and TSS with COD in Landfill - Endi Adriansyah; Brama Nalendra; Rifqi Sufra; Silvia Devi Eka Putri; M. Syaiful; Ari Setiawan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The increase in waste production, along with population growth, is filling landfills. Organic waste leachate formation. Leachate management is crucial because it can pollute soil, surface water, and groundwater. Waste is the solid remains of human activities and natural processes. Waste will be processed at the final processing site. Waste produces leachate due to decomposition and rainwater infiltration. Leachate testing requires laboratory analysis. Analysis can be done by measuring the physical and chemical parameters contained in leachate. Response Surface Methodology (RSM) is a statistical method for analysing data. This study determines the correlation between the main pollutant parameters, Temperature, pH, total suspended solids (TSS), and COD at the final treatment site. Data were collected from several sampling points over a period, and statistical analyses, including Pearson correlation and regression, were used to assess the relationship. The results showed a significant positive correlation with COD. The COD coefficient of determination (R-squared) of 66.74% was found to be quite high for all functional relationships, and mathematical models have been obtained. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and Communities